KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM PEMECAHAN MASALAH TRIGONOMETRI DITINJAU DARI KOMPETENSI PENGETAHUAN - Anwas Mashuri; Arum Dwi Rahmawati; Heri Cahyono (Universitas Muhammadiyah Semarang, 2019)
This study aims to determine the ability of verbal, visual, and symbolic mathematical representations in solving trigonometric problems. The subjects of this study were students of class XII IPA 1 Ngawi High School. This study uses a qualitative method. The data validation used in this study uses the time triangulation method. Analysis of the data used uses the stages of Huberman and Miles. The results of this study indicate that participants answered not only based on the numbers given, but also used the definition of trigonometric ratios on verbal representation. On the other hand, the subject is able to determine the position of the object to be observed. However, the subject failed to determine the direction of the depression angle in the sketch made on the visual representation. Failure to determine the direction of the angle of depression causes errors in using mathematical equations correctly. Finally, participants did not succeed in using mathematical equations correctly in symbolic representations. Based on some of the explanations above, we can recommend the importance of translation between mathematical representations and mathematical problems, as well as translations between mathematical representations (verbal, visual, and symbolic) in learning mathematics in class